"Rhetoric Mix" of Argumentations: How Policy Rhetoric Conveys Meaning of Entrepreneurship for Sustainable Development. (July 2020) - Salmivaara, Virva; Kibler, Ewald
Policymakers increasingly demand private enterprises to help solve social and ecological challenges faced by nations worldwide. In this article, we use Toulmin's rhetoric model to explain how European Union policy rhetoric articulates the meaning of entrepreneurship for sustainable development. Our findings demonstrate a "rhetoric mix" of argumentations through which policy rhetoric conveys three meanings of entrepreneurship—beneficiary in corrective sustainability, contributor in constructive sustainability, and opportunistic operator in assertive sustainability—and imposes shared beliefs that frame the policy discourse. In conclusion, we introduce a framework of "rhetoric mix" to advance research on entrepreneurship policy discourse and sustainable entrepreneurship.